2022
DOI: 10.1007/s10803-022-05739-0
|View full text |Cite
|
Sign up to set email alerts
|

Do Autistic People’s Support Needs and Non-Autistic People’s Support for the Neurodiversity Movement Contribute to Heightened Autism Stigma in South Korea vs. the US?

Abstract: We examined stigma towards vignette characters representing diverse autistic characteristics (social, non-speaking, or repetitive interests or restricted behaviors; RIRB) among 259 South Korean and 240 American participants (age range = 18 ~ 74). Within each domain, participants were randomized to read a vignette depicting low or high support needs. Koreans reported greater stigma towards autistic characteristics and less awareness of and support for the neurodiversity movement than Americans. Autistic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Based on these findings, Payne and Wood (2016) emphasized the importance of supplementing factual autism knowledge training with sensitivity training that increases understanding of the controllability of autistic characteristics. Some cross‐cultural studies suggest that attribution theory may be more relevant for understanding stigma toward autistic people in more culturally tight cultures such as China and South Korea (Kim & Gillespie‐Lynch, 2022; Lu et al, 2021). Yet, due to the lack of previous studies that referenced attribution theory as a theoretical motivation or specifically examined factors associated with attribution theory in the autism attitude literature, it is unclear how attribution theory aids the understanding of the association between knowledge and attitudes toward autistic people across cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, Payne and Wood (2016) emphasized the importance of supplementing factual autism knowledge training with sensitivity training that increases understanding of the controllability of autistic characteristics. Some cross‐cultural studies suggest that attribution theory may be more relevant for understanding stigma toward autistic people in more culturally tight cultures such as China and South Korea (Kim & Gillespie‐Lynch, 2022; Lu et al, 2021). Yet, due to the lack of previous studies that referenced attribution theory as a theoretical motivation or specifically examined factors associated with attribution theory in the autism attitude literature, it is unclear how attribution theory aids the understanding of the association between knowledge and attitudes toward autistic people across cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the perceived controllability (i.e., intentionality and responsibility of challenging behaviors) of disability‐related symptoms was found to reduce supportive emotions and helping behaviors toward disabled individuals (Schwarzer & Weiner, 1991). Although studies focused on attitudes toward autistic people have generally reported associations between knowledge and attitudes toward autistic people (Gillespie‐Lynch et al, 2019; Kuzminski et al, 2019), emerging evidence suggests that attribution theory may be more relevant for understanding attitudes toward autistic people in more culturally tight contexts, like South Korea and China (Kim & Gillespie‐Lynch, 2022).…”
Section: Knowledge‐related Theoriesmentioning
confidence: 99%
“…Indeed, previous studies have shown that Koreans have less accurate knowledge about autism than Americans (S. Y. Kim et al, 2022; S. Y. Kim & Gillespie-Lynch et al, 2022).…”
Section: Understanding the Cultural Context: South Koreamentioning
confidence: 99%
“…non-autistic individuals’) stigma toward both the label “autism” and unlabeled autistic characteristics is heightened in South Korea relative to the United States (S. Y. Kim et al, 2022; S. Y. Kim & Gillespie-Lynch et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation